Разговорно-просторечная лексика в „Материалах к словарю русского языка…” В.И. Прахова – российского филолога первой половины XIX века - Miakiszew, Władimir (Studia Rossica Posnaniensia, 2015)
This paper addresses the lexicographic work of V.I. Prakhov, who was a Moscow University graduate and a successful teacher in the 1830s and 1840s in the cities of Mogilev and Mstislavl. During this period, he compiled his (unfinished) Materials for an Explanatory Russian Dictionary, i.e. four books that contained “regional, colloquial, and archaic words which were mostly found in Old Russian and Western Russian memorabilia”. While describing the areas of V. Prakhov’s dictionary research, the paper focuses on the regional lexis that was captured in his manuscripts, i.e. the colloquial words and phrasemes of the Vologda Region.